Navigating the Dry Eye Therapeutic Puzzle: A Mechanism-Based Overview of Current Treatments - Jason Betz; Anat Galor (Pharmaceuticals)
Background/Objectives: Dry eye disease (DED) is a multifactorial condition with complex pathophysiology involving tear film instability, ocular surface inflammation, and nerve dysfunction. This review summarizes current evidence on the different available therapies targeting these mechanisms. Methods: A review of clinical studies evaluating treatment outcomes for therapies targeting aqueous tear deficiency, Meibomian gland dysfunction, ocular surface inflammation, and ocular pain was conducted, with an emphasis on randomized controlled trials and meta-analyses where available. Results: Artificial tears provide symptomatic relief with limited impact on tear film stability. Punctal plugs improve tear retention but show variable efficacy across studies. Treatments targeting MGD—such as lipid-based lubricants, eyelid hygiene, thermal pulsation (LipiFlow, iLux), and intense pulsed light (IPL)—demonstrate improvements in gland function, though outcomes vary. Anti-inflammatory agents including cyclosporine, lifitegrast, and short-term corticosteroids improve ocular surface signs, with mixed symptom relief. Biologic therapies like autologous serum tears and platelet-rich plasma show promise for both signs and symptoms, but data remain inconsistent. Nerve-targeted therapies, including oral neuromodulators (gabapentin, antidepressants), botulinum toxin, and transcutaneous nerve stimulation, have shown potential for managing neuropathic ocular pain, although randomized data are limited. Overall, variability in study designs, patient populations, and outcome measures highlights the need for more rigorous research. Conclusions: Personalized, mechanism-based treatment strategies are essential for optimizing outcomes in DED. Future research should prioritize well-designed, controlled studies to clarify the role of emerging therapies and guide the individualized management of this heterogeneous condition.